Is aspiration an effective acute stroke treatment in older adults? - Narloch, Jerzy; Piasecki, Adam; Ziecina, Piotr; Dȩbiec, Aleksander; Wierzbicki, Marek; Staszewski, Jacek; Piasecki, Piotr (Frontiers in Neurology, 2023)
Introduction: Clinical outcomes after interventional stroke treatment rely on numerous factors, with elderly age being associated with poorer results, mainly attributed to comorbidities and medications. The delivery of aspiration catheter would be hindered by carotid tortuosity, which is more prevalent with increasing age. In this study, we aimed to compare the clinical and angiographical outcomes of a direct aspiration first-pass technique in interventional stroke treatment in the elderly compared to younger patient groups. Materials and Methods: 162 patients (92 women and 70 men, aged between 35 and 94 years +/- 12.4 years) were included in this study Patients treated in a comprehensive stroke center due to large vessel occlusion stroke using aspiration as first-choice treatment were included in the study. To evaluate carotid arteries Tortuosity index (TI) was calculated for each segment of each carotid pathway. Results: Age correlated significantly with the presence of carotid tortuosity (R=0.408, p=0.000), extracranial length ratio (R=0.487, p=0.000) and overall length ratio (R=0.467, p=0.000). No significant associations were found with coiling, kinking or intracranial length ratio. Successful aspiration-based recanalization rate decreased with increasing age, the differences between age subgroups were not statistically significant. Comparison of extreme subgroups, ie. <60 years old vs >=80 years old, did not yield a statistically significant change (p=0.068). Conclusions: Successful aspiration-based recanalization rate decreased with increasing age; however, these differences were not significant. Clinical outcomes did not significantly differ with regard to carotid tortuosity, regardless of the time of assessment. Intracranial nor extracranial tortuosity were significantly associated with reperfusion-related complications in either of age subgroups.